Evaluation of smoking technique towards food preservation / Siti Aishah Rashid and Safiyyah Shahimi - Rashid, Siti Aishah; Shahimi, Safiyyah (2021)
Smoking technique has gained attention among the food industry players in extending the shelf life of the food products and maintaining the quality. Since most research involving the food smoking techniques was only focusing on the biological evaluation of smoked meats, this review highlights some chemical and biological quality evaluation of smoked food products. The effects of smoking technique with or without general-curing on the microbial population and pH of the smoked food products were evaluated. The bacterial number of Salmonella sp. was reduced along the processing chains from raw food to smoked food and cured smoked food with some negative detection after the smoking. Besides that, the significantly decreased pH (p<0.05) of the smoked food product has benefited the food preservation condition. Smoking technique with curing showed a decreasing trend on the bacterial population which increased the product shelf life. Hence, the smoking technique is recommended for extending the shelf life of food considering the initial microbial and also the food properties before and after smoking. This review will be a significant endeavour to the smoked food sellers and the consumers with an upgraded quality of food.